ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MEMILIH PROGRAM STUDI MANAJEMEN ZAKAT DAN WAKAF FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SUNAN AMPEL SURABAYA - Mustofa, Mustofa; Khotib Khotib (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This research aims to determine the factors that influence students' interest in choosing the Zakat and Waqf Management Study Program. The population of this research is all students of the Zakat and Waqf Management study program class of 2021, 2021, 2023 and 2024, totaling 264 students and the sample used is 157 people, however Only 107 people filled out or returned the questionnaire, so the sample used in this study was 107 people. This research is quantitative research with a descriptive statistical approach and the method used is a survey. The validity test uses Product Moment correlation and the reliability test uses Cronbach's alpha and the data analysis technique uses descriptive analysis with percentages. The research results show that there are six factors that are the most dominant in influencing students' interest in choosing the Zakat and Waqf management study program. The influence of each factor that influences students' interest in choosing a zakat and waqf management study program is a) the family support factor has an influence of 17.9%, b) the educational facilities factor has an influence of 16.95% c) the education cost factor has an influence of 16.60% . d) The job opportunity factor has an influence of 16.52%, e) The study program accreditation factor has an influence of 16.4% f) The self-encouragement factor has an influence of 16.30%